2019
DOI: 10.23887/jet.v3i1.17958
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Model Eliciting Activities terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMP

Abstract: Penelitian ini bertujuan untuk mengetahui apakah prestasi belajar matematika siswa yang dibelajarkan dengan model eliciting activities lebih tinggi daripada prestasi belajar matematika yang dibelajarkan dengan pembelajaran konvensional. Populasi dalam penelitian ini adalah siswa kelas VIII Non Unggulan SMP Negeri 1 Singaraja pada semester II tahun ajaran 2017/2018 yang tersebar ke dalam 7 kelas. Sampel penelitian ditentukan dengan teknik cluster random sampling. Peneliti telah menguji kesetaraan popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The results obtained by researchers have a relationship with the results of previous studies conducted by Sarah Nurshiami Sopandi, the results of his research showed that increasing the critical thinking skills of students who obtained model-learning activities (MEAs) increased (Delfia, et all, 2020). Furthermore, research conducted by S A Aziz and I Irawan which results of the research show that mathematics learning tools based on the MEAS approach can improve students' creative thinking abilities ( Aziz, S. A., & Irwan, I, 2020), Research from Made Juniantari states that there is a positive influence on the eliciting activities model on students' mathematics learning achievement (Juniantari, 2019), Subsequent research from Zairisma, et al with the results of his research that the mathematical representation ability of students taught using MEA with STAD type is better than conventional learning (Graphs, 2020), research from Rema Anggralia, et al whose research results show that there is a significant effect of the MEAs approach to students' mathematical communication skills (Anggralia et al, 2019), research from Winda, Sufyani and Elah shows that the Model Eliciting Activities (MEAs) can be one of the approaches used to improve students' mathematical creative thinking abilities (Winda et al, 2018), Other research conducted by Irwan, Asmar and Syarifuddin concluded that the learning process based on the MEAs approach applied to class X students in the first semester was valid, practical and effective (Irwan et al, 2018), Furthermore, research from Nina Santia et al can be concluded that the application of contextual-based Eliciting Activities (MEAs) models can improve students' mathematical understanding abilities and contextual-based Eliciting Activities (MEAs) models are more effectively used compared to conventional learning (Pemahaman & Siswa, 2020), the research from Pertamawati and Retnowati, the research shows that the implementation of MEAs is able to prepare students to solve real-life problems in the future by applying mathematical concepts that have been learned in school (Pertamawati & Retnowati, 2019), and finally research from Setiani, Waluya and Wardono shows that MEAs learning using the MT approach achieves both quantitative and qualitative criteria for student self-efficacy (Setiani et al, 2018).…”
Section: Data Analysis Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained by researchers have a relationship with the results of previous studies conducted by Sarah Nurshiami Sopandi, the results of his research showed that increasing the critical thinking skills of students who obtained model-learning activities (MEAs) increased (Delfia, et all, 2020). Furthermore, research conducted by S A Aziz and I Irawan which results of the research show that mathematics learning tools based on the MEAS approach can improve students' creative thinking abilities ( Aziz, S. A., & Irwan, I, 2020), Research from Made Juniantari states that there is a positive influence on the eliciting activities model on students' mathematics learning achievement (Juniantari, 2019), Subsequent research from Zairisma, et al with the results of his research that the mathematical representation ability of students taught using MEA with STAD type is better than conventional learning (Graphs, 2020), research from Rema Anggralia, et al whose research results show that there is a significant effect of the MEAs approach to students' mathematical communication skills (Anggralia et al, 2019), research from Winda, Sufyani and Elah shows that the Model Eliciting Activities (MEAs) can be one of the approaches used to improve students' mathematical creative thinking abilities (Winda et al, 2018), Other research conducted by Irwan, Asmar and Syarifuddin concluded that the learning process based on the MEAs approach applied to class X students in the first semester was valid, practical and effective (Irwan et al, 2018), Furthermore, research from Nina Santia et al can be concluded that the application of contextual-based Eliciting Activities (MEAs) models can improve students' mathematical understanding abilities and contextual-based Eliciting Activities (MEAs) models are more effectively used compared to conventional learning (Pemahaman & Siswa, 2020), the research from Pertamawati and Retnowati, the research shows that the implementation of MEAs is able to prepare students to solve real-life problems in the future by applying mathematical concepts that have been learned in school (Pertamawati & Retnowati, 2019), and finally research from Setiani, Waluya and Wardono shows that MEAs learning using the MT approach achieves both quantitative and qualitative criteria for student self-efficacy (Setiani et al, 2018).…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Several studies related to the Eliciting Activities Model that have been done previously by several researchers show that the Eliciting Activities Model is effective for improving students' critical thinking skills (Delfia, et all, 2020), think creatively ( Aziz, S. A., & Irwan, I, 2020), mathematics learning achievement (Juniantari, 2019), ability of representation (Graphs, 2020), mathematical communication skills (Anggralia et al, 2019), and students' mathematical understanding abilities (Santia, et all, 2020), mathematical creative thinking (Winda et al, 2018), the learning process based on the MEAs approach applied to class X students in the first semester is valid, practical and effective (Irwan et al, 2018), able to prepare students to solve real-life problems by applying mathematical concepts (Pertamawati & Retnowati, 2019), and MEAs learning using the MT approach achieves both quantitative and qualitative criteria for student self-efficacy (Setiani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%